Study on the effect of electric current intensity stimulation combined with biofeedback pelvic floor muscle training on postpartum pelvic floor dysfunction - Y.N. Zhou; Y.C. Teng; G.P. Gan (Clinical and Experimental Obstetrics & Gynecology)
Aim: To explore the effect of different electrical stimulation intensities combined with pelvic floor muscle training on postpartum pelvic floor dysfunction. Methods: 720 patients with pelvic floor dysfunction diagnosed following vaginal delivery were randomly divided into intervention and control groups. The control group was treated with conventional electrical stimulation combined with pelvic floor muscle training. Patients in the intervention group were treated with electrical stimulation of increasing intensity. The electrophysiological indices of pelvic floor function, SUI incidence, ICI-Q-SF, POP-Q, PFIQ-7 and PISQ-12 scores were compared between the two groups. Results: Following treatment, patients in the intervention group had significantly higher pelvic floor muscle type I, type II muscle strengths, slow muscle average myoelectric values, fast muscle maximum myoelectric values, front resting average myoelectric values, rear resting average myoelectric values, and vaginal resting pressure, compared to the control group. There was no difference in the Bp, D, GH, PB and TVL measurements between the two groups. SUI, ICI-Q-SF and PISQ-12 scores were significantly lower in the intervention group, but there was no difference in the PFIQ-7 score. Conclusion: Use of higher intensity electric stimulation combined with pelvic floor muscle training appears to improve the electrophysiological indices of pelvic floor function and POP-Q parameters, as well as reducing the severity and incidence of urinary incontinence and improving sexual function.